Development and Characterization of a Novel Spray-Dried Powder for Inhalation of Cinacalcet HCl Nanoparticles - Katayoon Mireskandari; Mostafa Rostamnezhad; Majid Darabi; Mohammadreza Rouini; Alireza Vatanara (Tabriz University of Medical Sciences, 2024)
Background: Administering Cinacalcet HCl (CINA) can be challenging because of its low oral bioavailability (20 to 25%) due mainly to its high first-pass metabolism and poor aqueous solubility. However, nanosuspensions are an effective way of enhancing solubility by reducing size. Furthermore, pulmonary delivery of the drug as a promising alternative route can bypass the hepatic first-pass metabolism. Method: A CINA nanosuspension was produced by sonoprecipitation and optimized to achieve minimum particle size and polydispersity index (PDI). These nanosuspensions were then spray-dried with different types of sugars to form nano-in-micro composite particles. The particles were then analyzed by scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transform infrared (FTIR), and differential scanning calorimetry (DSC), and the dissolution rate, solubility, and in vitro aerosol deposition behavior were determined. Results: The particle size of nanosuspensions was in the range of 239.5 to 1281.8 nm and the size was dependent on the process parameters. The spray-dried microparticles had a smooth and spherical surface morphology. The particle size of the composite particles was in the range of 2 to 10 µm and the dissolution rate of processed powders was significantly higher than raw CINA powder. Its crystallinity was partially diminished and no polymorphic conversion were observed. The in vitro deposition study, using a twin-stage impinger (TSI), presented fine particle fractions up to 76.7 percent. Conclusion: The utilization of nano-in-micro composite particles as a pulmonary delivery system for CINA has shown great potential in enabling a more efficient drug delivery.